(3JGL GdCRjGL hZfjI GdeMJGLs - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj,J (B680 (3g` s ((3YHO GdYRjR Hf eSYhO Hf YHO GdYRjR GdJdeSGfi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdPhGJ bGd jMji Hf eMeO Hf CHj GdTcQ GdeZQHi (B: (3Efg deG cGfJ UfGYI MSGH MQcGJ GdfLhe ef CLd GdYdhe TQYJ ai Yed cJGH ajgG s
(3BNQgG (B:s
(3hJCNQ GdaUd HjfeG Ef cGf ef LgJjf eNJdaJjf eeG MUd ef Pdc agh YQV GdbeQ hgPG GdHGH NGJeI cJGHfG HJeGeg cJHg jMji Hf eMeO Hf CHj GdTcQ GdeZQHi GdCfOdSi , HeOjfI OeTb GdeMQhSI SfI s
(3Cdag GdeDda ai OeTb SfI (B657(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B166 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B516s
Keywords: (3Gdadcs